Karakteristik Pimpinan, Inovasi, dan Kesadaran Kewajiban Pajak Perusahaan - R. Rosiyana Dewi; Abubakar Arif; Seto Makmur Wibowo; Eka Pujianthi; Mauliddini Nadhifah (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2022)
A company is taxed based on the profits it earns as part of its contribution to building the nation. The characteristics of leaders in a company as part of the company's management can affect the value of corporate tax liability awareness, as well as innovations that can become a burden for the company can also affect tax liability awareness. This study aims to see the effect of gender, tenure, and innovation on awareness of tax obligations. The population in this study is the manufacturing industry sector companies listed on the Indonesia Stock Exchange in 2015-2019, which were selected using the purposive sampling method, so that the total sample is 85 annual reports. This research is a quantitative research by testing the hypothesis. Hypothesis testing using panel test with eviews 9.0 tool. This study accepts two of the three hypotheses, namely female gender has a positive effect on awareness of tax obligations and tenure also has a negative effect on awareness of tax obligations, while the effect of innovation on tax awareness cannot be proven in this study. A person's behavior is influenced by his rational mind (the theory of planned behavior), a woman has a risk aversion background, while a too long tenure can increase her ability to understand information gaps and the ability to master.